TYPE OF ACCOMODATION IN RURAL AREAS IN SERBIA AND CHALLENGES IN FUTHER RURAL TOURISM DEVELOPMET - Bejatović, Gordana; D. Bugarčić, Marina; D. Bugarčić, Jovan (Economics of Agriculture, 2025)
This study explores tourists’ accommodation preferences in rural areas of Serbia, aiming to identify the most frequently used types of lodging, key decision-making factors, and potential differences across demographic groups. The research is based on a survey of 250 respondents conducted in March 2024, with data analyzed using descriptive statistics, t-tests, and ANOVA. Results show that tourists most often choose household-based accommodation and hotels, with location, equipment, and accessibility being the most influential factors. No statistically significant differences were found across gender, age, or education level. The study highlights the dominance of short domestic stays, limited influence of digital platforms, and a high share of informal accommodation practices. Findings suggest the need for investment in infrastructure and support for formalizing rural tourism services. The research contributes to understanding rural tourist behavior and offers practical insights for improving rural hospitality offerings in Serbia.